114k views
4 votes
9x + y = 9 3x + 3y = -12

User Sneaksta
by
4.7k points

1 Answer

4 votes

Answer:

x = 13/8

y = -45/8

Explanation:

9x + y = 9

3x + 3y = -12

Divide the second equation by 3

x+y = -4

Multiply this by -1

-x -y = 4

Add this to the first equation to eliminate y

9x + y = 9

-x -y = 4

-----------------

8x +0 = 13

Divide by 8

8x/8 = 13/8

x = 13/8

Now find y

x+y = -4

13/8 +y = -4

Subtract 13/8 from each side

13/8 -13/8 +y = -4-13/8

y = -32/8 - 13/8

y = -45/8

User Laurent VB
by
4.5k points